Simulation study on fueling depths of pellet injection and compact torus injection in CFEDR plasma - ZHANG, Jie; YE, Yang; TAN, Mingsheng; HUANG, Jia; CHEN, Jiale; ZHANG, Ling; XU, Guoliang; ZHANG, Yang; YANG, Lixiang; ZHAO, Zhihao; KONG, Defeng; DING, Rui; et al. (Plasma science & technology, 2025)
In this research, a simulation study is conducted on the fueling depths of pellet injection (PI) and compact torus (CT) injection in the China Fusion Engineering Demo Reactor (CFEDR) plasma. For PI, the HPI2 code is employed to simulate the ablation and deposition processes under diverse injection parameters. Results show that the penetration depth of pellets is relatively shallow in the CFEDR plasma compared to existing tokamaks. The B -induced drifts of plasmoids play a significant role in enhancing the fueling depth; however, the plasmoid drift tends to be reduced as the pellet size is increased. Increasing the injection speed can remarkably increase the penetration and deposition depths. However, high-speed PI causes greater perturbation to the core plasma, and its impact on fusion performance needs further assessment. The physical design of a CT fueling system for the CFEDR is also presented in this paper. The proposed CT injector fires 0.7 mg CT clusters of D–T (1:1) fuel, with an electron density of 1.78×10 22 m −3 , into the CFEDR at a rate of up to 50 Hz. The injection velocity is 215 km/s, targeting a penetration depth at the CFEDR normalized radius of 0.7. Similarly, the injection of CT plasma at such a high velocity and frequency may also affect the discharge of the main plasma, which remains to be further verified through simulations and experiments. Overall, this study provides important data support and theoretical guidance for exploring high-density operation modes in CFEDR plasma, and is expected to contribute to the development of future fusion devices.